2016
DOI: 10.25229/beta.266928
|View full text |Cite
|
Sign up to set email alerts
|

1960-2010 Döneminde Türkiye’den OECD Ülkelerine Gerçekleşen Göçün Çekim Modeli ile Analizi

Abstract: For several decades international migration is one of the most important issues of the global agenda which causes significant economic and social changes in both source countries and host countries of migration. The economic reasons of international migration can be analyzed with the Gravity Model effectively and elaborately. In this study, we analyze the economical determinants of immigration to the 20 OECD countries from Turkey over the 1960-2010 period with an augmented Gravity Model. Results of the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Essentially the studies using gravity model is not included the same factors due to having flexible qualification or augmented form of gravity model. In terms of the income factor, in generel review, studies found that people migrate for a higher level income (Karemera et al 2000;Clark et al 2007;Dinçer and Muratoğlu, 2014;Muratoğlu and Muratoğlu, 2016;Zülfikar Savcı, 2016;Dedeoğlu and Genç, 2017;Çetin, 2019;Koç and Solmaz, 2019). This proof is coherent with assumption of the gravity model.…”
Section: Empirical Literature Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Essentially the studies using gravity model is not included the same factors due to having flexible qualification or augmented form of gravity model. In terms of the income factor, in generel review, studies found that people migrate for a higher level income (Karemera et al 2000;Clark et al 2007;Dinçer and Muratoğlu, 2014;Muratoğlu and Muratoğlu, 2016;Zülfikar Savcı, 2016;Dedeoğlu and Genç, 2017;Çetin, 2019;Koç and Solmaz, 2019). This proof is coherent with assumption of the gravity model.…”
Section: Empirical Literature Reviewmentioning
confidence: 54%
“…If we handle the population factor symbolising a demographic determinants, it is pointed in the studies that population is generally significant for migration decision. However population in origin and destionation region differs in terms of the result (Karemera et al 2000;Clark et al 2007;Dinçer and Muratoğlu, 2014;Muratoğlu and Muratoğlu, 2016;Koç and Solmaz, 2016;Dedeoğlu and Genç, 2017). That situation is likely related to meaning of population.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…A few studies questioned the determinants of international migration flows of Türkiye in the framework of the gravity model. Analysing the bilateral migration flows from Türkiye to OECD countries for the period 1960–2010, Muratoğlu and Muratoğlu (2016) concluded that the economic size of OECD countries and the population size of Türkiye are positively associated with emigration flows; on the other side, the economic size of Türkiye and population size of OECD countries are negatively associated with them. In addition, the study reached evidence of the discouraging impact of distance on this type of migration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gelir, nüfus ve mesafe faktörü açısından Abel vd. ( 2019), Agbola ve Acupan (2010), Dedeoğlu ve Genç (2020), Çetin (2019), Iancu (2017), Köseoğlu ve Artan (2020), Muratoğlu ve Muratoğlu (2016) ve diğer birçok çalışma ile benzer sonuçlar elde edilirken; sosyal ağlar, göçmen stoku, dil ortaklığı, istihdam ve işsizlik faktörü bakımından Abel vd. ( 2019), Clark vd.…”
Section: Bulgularunclassified